Oral and vaginal route of misoprostol for induction of labour: a comparative study - Sharma, Deepti D.; Chandnani, Kavita A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Induction of labour can be defined as “Artificial initiation of uterine contractions before the onset of spontaneous labour, after the period of viability, by any methods, for purpose of vaginal delivery.” The key factor for a successful induction is the status of cervix, its form, consistency and dilatation which is determined by the Bishop score. In case of unfavourable cervix or in the pregnancies remote from the term; prostaglandins are more effective than any other method of induction. Introduction of misoprostol, PGE1 analogue, for the induction of labour in 1993 and its approval for clinical use by ACOG (American College of Obstetrics and Gynecology) in 1999 has been the most significant advancement. It is the latest drug for induction of labour which is cheap and stable at room temperature and is being used worldwide in different doses and by various routes. We compared the most commonly preferred two routes; vaginal and oral in terms of success of induction and noted the adverse events and side effects in both routes. Methods: This was a prospective comparative study carried out at SBKSMIRC (Shrimati Bhikhiben Kanjibhai Shah Medical Institute and Research Centre), Dhiraj general hospital, Vadodara, Gujarat, 200 patients who required induction of labour were recruited after applying inclusion and exclusion criteria and were randomly divided in two groups- Group A meant to receive 50µg oral misoprostol, Group B - meant to receive 25µg vaginal misoprostol repeated 4 hourly up to maximum of five doses. Progress of labour was charted on the partograph. The mean induction delivery interval, mode of delivery, maternal and neonatal outcomes and complications were observed. Results: The mean induction to delivery interval was significantly less in vaginal group than oral (23.3±12.4 hours in oral vs. 17.3±10 hours in vaginal). Vaginal delivery and cesarean section rates were comparable in both groups (76% in Group A vs. 72% in Group B for vaginal delivery, 18% vs. 20% for Cesarean section, respectively). 58% patients in Group A required more than two doses as compared to 39% in group B, though the difference was statistically not significant. Significant number of patients required added oxytocin administration in Group A (72%). No major complications or adverse events were observed. Neonatal hyperbilirubinemia was seen more in Group A. Conclusions: Both Oral misoprostol in a dose of 50μg and vaginal misoprostol 25 μg every four hours, to a maximum of five doses, have the potential to induce labour safely and effectively. The vaginal route however is beneficial in effecting delivery in lesser time with few numbers of doses as compared to oral route.